Discussions on Business Networks Research Methodology Present in a Sample of Brazilian Scientific Production and Proposal for a Guiding Model - Giglio, Ernesto Michelangelo; Hernandez, José Luís Guagliardi (Review of Business Management, 2012)
The aim of this article is to discuss the business network research methodologies used by Brazilian authors based on a sample of the scientific production of the EnAnpad Congress. Our main hypothesis, which results from previous reflections, states that Brazilian researchers predominantly use classic methodologies of disjunction and reduction of the phenomenon, in search of strict causal relations that include study objects as actors. That approach explains the poor theoretical progress in that field. To reach our goal, we researched the international literature on networks focusing on the convergences of affirmatives, which are the base for the discussions. Among those, the flows as study object and the constant dynamics of networks stand out, which makes it difficult to establish strict causal relations. The convergences revealed two paradigms: on one hand, the rational economic paradigm that includes theories on transaction costs and network strategies and on the other hand, the social paradigm that includes theories on the network society and social relations defining the processes and controls of the technical relations of the network. We accepted and took the premises of those paradigms as a base to analyze the articles published by the EnAnpad Congress in last the ten years and concluded that our hypothesis is valid. The economic rational paradigm shows to be predominant, with its classical collection and analysis methods, as well as its questionnaires and interviews on attitudes and perceptions used to research strict causal relations and not yielding any theoretical benefits or progress. We understand that a different methodological approach may be applied, which we consider more appropriate to cover network features and which is based on the network society theory, taking into account the epistemological principles of the theory of complexity, mainly the nondisjunction principle and the use of the methods and techniques that result from the theory of the systems, especially the feedback theory. Based on those principles, we made up a research design project that integrates the subsystem of social relations with the subsystem of production relations, which is a fundamental principle of the social network approach, defining the flow between the actors as the study unit. In this system, historicity, flow, mobility and uncertainty are highlighted, which are the most outstanding features of the network phenomenon. Key words: Networks. Methodology. Research.